Manganese/bipyridine-catalyzed non-directed C(sp3)–H bromination using NBS and TMSN3 - Sneh, Kumar; Torigoe, Takeru; Kuninobu, Yoichiro (Beilstein Journal of Organic Chemistry, 2021)
A Mn(II)/bipyridine-catalyzed bromination reaction of unactivated aliphatic C(sp3)−H bonds has been developed using N-bromosuccinimide (NBS) as the brominating reagent. The reaction proceeded in moderate-to-good yield, even on a gram scale. The introduced bromine atom can be converted into fluorine and allyl groups.
Keywords: bromination; C–H transformation; hydrogen abstraction; manganese; radical